New collaborative DDoS defense technology based on NFV - Chuanfeng XU; Hui LIN; Xuancheng GUO; Xiaoding WANG (网络与信息安全学报)
To solve the problem of selfish behavior for self-security due to limited resources in the process of resisting distributed denial of service (DDoS) attacks by a collaborative network built with network function virtualization (NFV) technology,a new collaborative DDoS defense network model was proposed.a repeat prisoner's dilemma game model was built in the collaborative network,a reward and punishment incentive mechanism was introduced to strengthen the cooperation of the collaborative network,and a dynamic resource allocation mechanism based on social reputation value assessment was adopted.Simulation results show that the new collaborative DDoS attack defense technology outperforms existing solutions in terms of packet loss rate,cooperation,and resource allocation rate,improving the effectiveness of DDoS attack defense.